2014
DOI: 10.7785/tcrt.2012.500404
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Hydroxycamptothecin-encapsulated Chitosan Nanospheres for the Treatment of Liver Cancer

Abstract: Hydroxycamptothecin-encapsulated chitosan (HC) nanospheres were prepared by Shirasu porous glass (SPG) membrane emulsification technique. The properties and morphology of HC nanospheres were characterized. The diameter of the nanospheres could be controlled within a narrow distribution according to the pore-size of SPG membrane. Hydroxycamptothecin (HCPT) encapsulation efficiency could reach to 81.3%. The long-term drug release of HCPT could be presented by an accumulated drug release of 85.4% in 15 days with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…195,196 Studies have shown that chitosan NPs prolong the duration of HCPT administration, improve oral bioavailability, and improve antitumor effects while reducing side effects. [197][198][199] Positively charged chitosan NPs exhibited slow-release behavior, ensuring higher intracellular drug concentrations and more significant cytotoxicity. 200 FA-modified chitosan nanoneedles (Figure 5) and micelles exhibit significantly enhanced cellular uptake, higher cytotoxicity against folate-receptor-positive tumor cells.…”
Section: Chitosan-based Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…195,196 Studies have shown that chitosan NPs prolong the duration of HCPT administration, improve oral bioavailability, and improve antitumor effects while reducing side effects. [197][198][199] Positively charged chitosan NPs exhibited slow-release behavior, ensuring higher intracellular drug concentrations and more significant cytotoxicity. 200 FA-modified chitosan nanoneedles (Figure 5) and micelles exhibit significantly enhanced cellular uptake, higher cytotoxicity against folate-receptor-positive tumor cells.…”
Section: Chitosan-based Npsmentioning
confidence: 99%
“…In vitro and In vivo [183] Electrospun fibers-based NPs Chemotherapy In vivo [185,192] Chemotherapy In vitro and In vivo [186][187][188]190] Polysaccharide-based (Chitosan) NPs Chemotherapy In vitro [197,199] Chemotherapy In vitro and In vivo [198,[201][202][203] Chemotherapycombined with Gas Therapy In vitro and In vivo [ In vivo [284] Chemotherapy In vitro and In vivo [281,282,285,286] Chemotherapy combined with PDT In vitro and In vivo [278,279] https://doi.org/10.2147/IJN.S377149…”
Section: Chemotherapymentioning
confidence: 99%
“…Hydroxycamptothecin (HCPT) loaded chitosan nanospheres (average size of about 330 nm) were prepared using the membrane emulsification technique [60]. HCPT is an alkaloid isolated from the Camptotheca acuminate in China.…”
Section: Drug Loaded Chitosan Nanoparticlesmentioning
confidence: 99%
“…These NPs induced receptor-mediated endocytosis and also have prolonged blood circulation time, enhanced liver accumulation and reduced side effects, such as cardiotoxicity associated with doxorubicin [68]. In a related study, Han and colleagues [69] demonstrated that hydroxycamptothecin, a camptothecin derivative, could also reduce tumor weights and growth rates of liver cancer in vivo, when encapsulated in chitosan (HCS) NSs [69].…”
Section: Nk911mentioning
confidence: 97%